The positive impact of Internet on the cognitive, psychological and social side of people’s personality with disabilities - Vouglanis, Taxiarchis; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The purpose of the present study was to indicate the positive effects of internet in the personality of the person with disabilities. Through literature review was found that internet improves the cognitive (reading, writing, internet’s use), social (cooperation, friendship) and psychological skills (anxiety, stress, self-esteem). In conclusion, internet, computers’ technology and e-learning are creating multiple effects in all aspects of people’s personality with disabilities.